Sams teach yourself game programming in 24 hours - Morrison, Michael, 1970- (Sams teach yourself in 24 hours series., 2003)
Teaches fundamental C and C++ programming and provides information for programming games in Windows, exploring topics including game theory, double-buffered graphics, sprite animation, and digitized sound effects.